Spiritual leadership and organizational commitment: The mediation role of workplace spirituality - I Ketut Setia Sapta (Cogent Business & Management, 2021)
There is a shift in organizational focus from purely economic and social activities towards spiritual development. This phenomenon places spirituality as part of the development of holistic human resources. This study examined workplace spirituality’s role as a mediating variable in the spiritual relationship of leadership and organizational commitment. The survey was conducted on 200 employees in three public sector organizations in Bali Province, Indonesia. The data analysis used the Partial Least Square (PLS) approach. The results show that workplace spirituality can mediate the effect of spiritual leadership on organizational commitment. Theoretically, the findings imply that workplace spirituality is one of the factors considered in organizational theory. Practically, this finding provides insight into the leadership to pay attention to the employee’s spiritual needs. The results have implications for policy-makers to support and develop spirituality practices in the workplace.